Heavy grazing effects on stem elongation and internode allometry: Insights from a natural pasture grass. (5th March 2019) - Liu, Zhiying; Zhang, Zhen; Zhang, Tianyu; Gao, Ruofan; Li, Xiliang
Abstract: Limited plant stem elongation is hypothesized to be the primary cause of decreased plant growth in response to long‐term heavy grazing (LHG). However, it remains largely unknown how LHG‐induced changes in stem elongation are mediated by internode traits. Accordingly, we experimentally investigated the effects of LHG (defined as twice the stocking rate recommended by the local government) on plant stem elongation and internode allometry in Leymus chinensis in Xilinhot, Inner Mongolia, China. Plant size and internode traits, including internode length (IL), internode diameter (ID), and internode number (IN), from plant individuals were measured according to their phytomer position from base to apex. The results revealed that IN and their distributions were changed in response to LHG. Although LHG negatively affected IL and ID of each L. chinensis internode from base to apex and eventually stem length, the plasticity index of IL and ID increased initially and then decreased from the lowermost to the uppermost internode in response to LHG. These contrasting responses of internode traits were result of allometry between internode traits determined by both LHG and internode position. Ultimately, IL and IN were identified to be key traits influencing stem length reduction under LHG conditions and explaining 52.51% and 47.49% of variation in stem length, respectively. Overall, our findings suggest that the limitation of L. chinensis stem elongation induced by LHG is mediated by the plasticity and allometry of internode traits. This result emphasizes the sensitivity of individual plants to LHG and is potentially valuable for optimal grassland management.